Geodetic boundary value problem : the equivalence between Molodensky's and Helmert's solutions /: the equivalence between Molodensky's and Helmert's solutions. ([2016]) - Sansò, F (Fernando), 1945-; Sideris, Michael G, 1958-
No abstract available